Analysis of enantiomers and regioisomers of triacylglycerols using supercritical fluid chromatography - Naotunna Palliya Guruge, Dilakshi Navoda (My University, 2024)
The diverse structural nature of lipids present in real biological samples contributes to the complexity of lipid analysis, necessitating the use of sophisticated analytical methods. Supercritical fluid chromatography (SFC) in lipid analysis has gained more attention since it is known to be a low-cost and eco-friendly technique and can be applied to separate even isomeric lipid species. This study aimed to develop and optimize a method to analyze enantiomers and regioisomers of selected triacylglycerols (TAGs). The subcritical fluid chromatographic technique with mass spectrometric detection was applied with 2 similar CHIRALPAK® IG-U columns in series. The optimized method was then applied to find the relative abundance of OOP and OPP isomers in selected plant oils (olive oil, rapeseed oil, oat oil, sunflower oil, avocado oil and rice bran oil). Optimal SFC conditions were identified through experimentation, resulting in a method that could successfully separate TAG isomers such as sn-OOP/sn-POO/sn-OPO, sn OPP/sn-PPO/sn-POP, sn-MPO/sn-OPM, and sn-OPS/sn-SPO. However, the optimized method did not separate TAG isomers; sn-OPL/sn-LPO and sn-LaPO/sn-OPLa. The results indicate that in plant oils, unsaturated fatty acids (FAs), such as oleic acid, are predominantly esterified at the sn-2 position of the glycerol backbone, confirming the non-random positional distribution of naturally occurring FAs. This novel chiral SFC method offers a valuable approach for the simultaneous analysis of TAG enantiomers and regioisomers in natural samples, essential for understanding their metabolic, nutritional, and technological properties.
Keywords: enantiomers, mass spectrometry, method development, plant oils regioisomers, supercritical fluid chromatography, triacylglycerols